(3hQTI Yed ddJYQja HGdJhUjI GdOhdjI HTCf ChVGY GdeOQSjf GdJj CbQgG GdeDJeQ GdOhdj GdMchej GdNGU HTCf ChVGY GdeOQSjf GdefYbO HOYhI ef GdjhfSch hefXeI GdYed GdOhdjI aj HGQjS, HJGQjN (B5 (3JTQjf GdChd (B/ (3CcJhHQs - (3hQTI Yed ddJYQja HGdJhUjI GdOhdjI HTCf ChVGY GdeOQSjf (B(2007: (3HjQhJs ((3HjQhJs (3GdjhfSchs, 2007)
(3jJfGhd gPG GdcJGH GMOGK hQTI GdYed GdPj YbOJ aj HjQhJ (B17 (3THGW (B2007. (3hJVef GdcJGH YfGhjf ChQGb GdeOGNdGJ hedGMXGJ GdhRjQ NGdO bHGfj(B. (3hef Ke GdJhUjGJ GdJj GfJgJ HgG hQVI GdYed gPg(B.s
(3GdfhY (B: (3cJGHs
Keywords: ONU; Statut des enseignants; Teachers Status; UN; (3GdCee GdeJMOIs; (3ChVGY GdeYdejfs